The Mongol world
1 online resource.
Keywords: "Drawing upon research carried out in several different languages and across a variety of disciplines, The Mongol World documents how Mongol rule shaped the trajectory of Eurasian history from Central Europe to the Korean Peninsula, from the thirteenth century to the fifteenth century. With 58 chapters written by both senior and early-career scholars, the volume is an essential resource for all students and scholars who study the Mongol Empire from its origins to its disintegration and legacy"--